EFL STUDENTS' PERCEPTION OF USING GOOGLE CLASSROOM AND GOOGLE MEETING IN ONLINE LEARNING - Vina Fathira (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Teachers should teach and transfer knowledge successfully in online learning, despite the fact that it is still a pandemic. It is difficult because the teacher and students aren't in the same room. Combining Google classroom and Google meeting is one of the solution to help the learners get some knowledge even in in online learning class. This research can be a good input for the teacher to evaluate future learning better than before in EFL classroom during Covid-19 pandemic for online learning class. This study aims at EFL students’ perception of online learning for EFL students during the covid-19 Pandemic in online learning class. The method of the research was descriptively quantitative. The sample of this research was 13 students, collected by using total sampling. The tool for this study was a series of 20-question questionnaire delivered to students using Google Form. The students were asked to choose one of four options in the questionnaire to collect data. After getting the data based on the students’ answer in questionnaire, the data was analysed. The result of the research stated that the students’ perception about combining Google classroom and Google meeting in online learning was very helpful. However, only a few student was saying not effective in combining Google classroom and Google meeting because of the internet connection around his place. The conclusion of the research was the students’ perception in combining Google classroom and Google meeting was helpful to cover only a few part of learning process, like transferring knowledge, even though there are still many part of learning are missing even though by using Google classroom and Google meeting.